Optimal claiming strategies in Bonus Malus systems and implied Markov chains - Arthur Charpentier; Arthur David; Romuald Elie (Risks, 2017)
In this paper, we investigate the impact of the accident reporting strategy of drivers, within a Bonus-Malus system. We exhibit the induced modification of the corresponding class level transition matrix and derive the optimal reporting strategy for rational drivers. The hunger for bonuses induces optimal thresholds under which, drivers do not claim their losses. Mathematical properties of the induced level class process are studied. A convergent numerical algorithm is provided for computing such thresholds and realistic numerical applications are discussed.
Keywords: 330; bonus hunger; bonus-malus; control; incentives; Markov Chains; reporting